ANALISIS BED OCCUPANCY RATION (BOR) DALAM MENILAI TINGKAT EFISIENSI PEMAKAIAN TEMPAT TIDUR DI RUMAH SAKIT UMUM DAERAH CILILIN - Dea Syafira Aditia; Annisa Ulfah (Jurnal Infokes, 2023)
Health service indicators need to be observed, one of which is the efficiency of inpatient services. One way to measure hospital efficiency is to calculate four parameters: BOR, LOS, TOI, and BTO. Then, these parameters can be represented by Barber Johnson graphs. Objective: This study aims to analyze the efficiency level of bed usage at Cililin Regional General Hospital (RSUD) Method: The research used is descriptive quantitative method. The variables used are Average Length Of Stay (ALOS), Bed Occupancy Rate (BOR), Bed Turn Over (BTO) and Turn Over Interval (TOI). The sample used is in the form of recapitulation data from January to December 2022. Results: Based on the results of the study from January to December it was found that January to August were outside the efficient line. One of the reasons was the aftermath of Covid-19. Conclusion: through the Barber Johnson chart at Cililin Hospital, West Bandung Regency, from September to December 2022, the use of beds in inpatient rooms has met Barber Johnson’s minimum standards. Keywords: Efficient use of beds, Barber Johnson Chart